2018
DOI: 10.3892/ijmm.2018.3939
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cyclooxygenase 2 increases chemosensitivity to sesamin through the Akt‑PI3K signaling pathway in lung cancer cells

Abstract: Safe, affordable and efficacious agents are urgently required for cancer prevention. Sesamin, a lipid-soluble lignan from sesame (Sesamum indicum) displays anticancer activities through an unknown mechanism. In the present study, the anticancer activity of sesamin via cyclooxygenase 2 (COX2) was investigated in lung cancer. Quantitative polymerase chain reaction was performed to determine the mRNA expression levels of COX2 in cells, while western blot analysis was used to determine its protein expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…This action of sesamin showed that the lignan is capable of preventing DNA damage, hence, it becomes a potential anticancer agent. In line with this, it was also reported that the ability of sesamin to reduce COX-2 gene expressions in A549 cell line occurs through PI3K-Akt pathway [135] and inhibition of this pathway inactivates inflammatory response, which reduces restenosis [136].…”
Section: Lung Cancermentioning
confidence: 57%
“…This action of sesamin showed that the lignan is capable of preventing DNA damage, hence, it becomes a potential anticancer agent. In line with this, it was also reported that the ability of sesamin to reduce COX-2 gene expressions in A549 cell line occurs through PI3K-Akt pathway [135] and inhibition of this pathway inactivates inflammatory response, which reduces restenosis [136].…”
Section: Lung Cancermentioning
confidence: 57%
“…Sesamin is a lignin component isolated from sesame oil and is commonly considered a healthy food with antihypertensive, antiinflammatory, antiviral and antioxidative properties (Xu et al 2015). Additionally, the potential anticancer properties of sesamin in lung cancer, cervical cancer, and colon cancer have been reported in recent years (Dou et al 2018;Cavuturu et al 2019;Fang et al 2019). Previous evidence has shown that sesamin can inhibit lipopolysaccharide (LPS)-induced expression of Toll-like receptor (TLR) 4, which further results in repression of the inflammatory response (Qiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that HNE induces the expression of the COX2 gene, and that this expression is stabilized by the p38 mitogen‐activated protein kinase . In addition, COX2 has been reported to be involved in PI3K/Akt signaling . Recently, it was reported that administration of HNE decreased Akt phosphorylation and induced apoptosis in an osteosarcoma cell line .…”
Section: Discussionmentioning
confidence: 99%